How Cognitive Skills Affect Strategic Behavior: Cognitive Ability, Fluid Intelligence and Judgment - David Gill; Zachary Knepper; Victoria L. Prowse; Junya Zhou (Institute of Labor Economics (IZA), 2024)
We explore the influence of cognitive ability and judgment on strategic behavior in the beauty contest game (where the Nash equilibrium action is zero). Using the level-k model of bounded rationality, cognitive ability and judgment both predict higher level strategic thinking. However, individuals with better judgment choose zero less frequently, and we uncover a novel dynamic mechanism that sheds light on this pattern. Taken together, our results indicate that fluid (i.e., analytical) intelligence is a primary driver of strategic level-k thinking, while facets of judgment that are distinct from fluid intelligence drive the lower inclination of high judgment individuals to choose zero.
Keywords: C92; C72; D91; 330; cognitive ability; judgment; fluid intelligence; matrix reasoning; beauty contest; strategic sophistication; level-k; experiment; game theory